PENERAPAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE DALAM PENGELOLAAN RUANG TERBUKA HIJAU DI PEMERINTAH KABUPATEN GRESIK - Citra Annisa Putri; Deby Febriyan Eprilianto (Universitas Negeri Surabaya, 2022)
The rapid development of industry, followed by an increasing population, has an impact on changes in land use. Green Open Space (RTH) is land that has an important role in an area. However, green open space in Gresik Regency has not yet reached the standard according to the regulations specified. This study aims to analyze and describe the management of green open space in the Gresik Regency government using a good environmental governance perspective with qualitative descriptive methods and data collection techniques carried out through interviews with various related information sources, direct field observations, literature studies and documentation in the form of photos and information. written. The research subjects involved the Head of the Gardening and Decoration Division, the Head of the Development Section for Decoration Improvement in the Gardening and Decoration Sector at the Environmental Service, 2 staff employees at the Environmental Service and 5 communities. The results of the study show that: 1) the rule of law, guided by the central and regional legal regulations, 2) participation and representation, the private sector and the community play a role in providing green open land in their environment 3) access to information, on local government websites and Instagram, 4) transparency and accountability, access to information through local government websites and accountability for the annual LKPJ, 5) decentralization, not yet strong enough but decision making is still carried out by the Regent, 6) institutions and institutions, does not have its own green open space agency but each part has carried out its duties in accordance with with its main duties and functions, 7) access to justice, complaints are made on the people's online complaint and aspiration service website as well as on the Gresik Regency public green open space which can be accessed by the public. The overall analysis is quite good but there are some aspects that are not optimal, namely decentralization. So there is a need for innovation from the Gresik Regency government. Keywords: Green Open Space (GOS), Local Government, Good Environmental Governance